EFISIENSI TEKNIS DAN FAKTOR YANG MEMPENGARUHI PRODUKSI PADI LOKAL SIGUPAI DI KABUPATEN ACEH BARAT DAYA (Technical Efficiency and Factors Affecting the Production of Local Sigupai Rice in Aceh Barat Daya Regency) - ULFA, MUNIRA; RAHMAN, HERI; YUSTIANA, YOOCE (Universitas Mulawarman (University of Mulawarman), 2024)
Sigupai rice is highly sought after and has significant economic value. Despite its popularity, the production of Sigupai rice remains relatively low. This study aims to identify the factors influencing the production, technical efficiency, and sources of inefficiency in Sigupai rice farming in West Aceh District. Data was collected from all 31 Sigupai rice farmers in the region and analyzed using the stochastic frontier Cobb-Douglas production function. The results indicate that Sigupai rice farming has achieved a technical efficiency level of 0.80. Land area, seed quantity, and fertilizer were found to significantly influence rice production. However, farmers' age, experience in cultivating Sigupai rice, and education did not have a significant impact on technical inefficiency.To improve the efficiency of Sigupai rice farming, it is recommended to optimize input utilization, including proper land planning and soil management. Additionally, the use of certified Sigupai rice seeds and efficient fertilization techniques can contribute to increased productivity.